An optimization model for the fair distribution of prize money in ATP tournaments - Govea, Z.; Pérez-Galarce, F.; Candia-Véjar, A. (International Journal of Computer Science in Sport, 2022)
The Association of Tennis Professionals (ATP) distributes a considerable amount of money in prizes each year. Studies have shown that only the top 100 ranked players can self-finance; hence, it is convenient to introduce changes to the prize distribution to promote a more sustainable system. A Linear Programming model to distribute the tournament`s budget under a new concept for the fair distribution of prize money is proposed. Additionally, to distribute the prizes, a function based on the effort of the players is designed. The model was applied to tournaments to demonstrate the impact on improving the player`s prizes distribution.